User Experience, Trust, and Service Usage Breadth as Determinants of Customer Satisfaction in Mobile Banking: A Mediation Analysis - Murmadoni Harahap; Adelina Lubis; Muhammad Yamin Siregar (Journal of Social Work and Science Education, 2026)
This study examines the mediating role of Breadth of Service Usage in the relationships between User Experience, User Trust, and Customer Satisfaction in the context of the Sumut Mobile application, a regional digital banking platform in Indonesia. Digital banking has become increasingly important in supporting financial inclusion; however, customer satisfaction depends on both the quality of users’ experiences and their trust in the digital banking system. Employing a quantitative associative research design, data were collected from 100 active users of the Sumut Mobile application through purposive sampling. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS version 4.1.4. The findings reveal that User Experience significantly influences Breadth of Service Usage (t = 3.823, p < 0.001) and Customer Satisfaction (t = 3.242, p = 0.009). Similarly, User Trust significantly affects Breadth of Service Usage (t = 5.996, p < 0.001) and Customer Satisfaction (t = 2.381, p = 0.017). Furthermore, Breadth of Service Usage significantly mediates the effects of User Experience (t = 3.417, p = 0.006) and User Trust (t = 3.521, p = 0.008) on Customer Satisfaction. These findings extend the Technology Acceptance Model literature by demonstrating that Breadth of Service Usage serves as an important mechanism through which positive user experiences and trust are translated into higher customer satisfaction. Practically, regional banks should improve user-interface design, strengthen perceptions of security and reliability, and encourage customers to utilize a broader range of digital banking features to enhance satisfaction and long-term loyalty.